2008
DOI: 10.4319/lo.2008.53.2.0867
|View full text |Cite
|
Sign up to set email alerts
|

The production of volatile iodocarbons by biogenic marine aggregates

Abstract: We present the first reported measurements of volatile iodocarbon production by biogenic marine aggregates. Iodomethane (CH3I), iodoethane (C2H5I), 2‐iodopropane (CH3CHICH3), and 1‐iodopropane (CH3CH2CH2I) concentrations were determined in incubations of aggregates formed by concentrating the >53 µm fraction of the plankton during a field campaign in the Celtic Sea. All four iodocarbons increased significantly in concentration in the aggregate incubations relative to filtered seawater controls. Maximum product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…The average C 2 H 5 I concentration (0.14 pmol l -1 ) was within the range of previously reported values (0.10-0.27 pmol l -1 ) in the Atlantic section of the Southern Ocean (50-60°S) during the austral summer (Abrahamsson et al, 2004). Hughes et al (2008) have reported that biogenic marine aggregates collected in the subarctic Atlantic water, including plankton concentrate, diatom mucilage, and phytodetritus, produce C 2 H 5 I at a high rate (0.31 pmol l -1 h -1 ). The high biological productivity in subpolar water containing high levels of biogenic aggregates would lead to a high rate of C 2 H 5 I production in seawater.…”
Section: Distributions Of C 2 H 5 I Concentration and Sea-to-air Fluxsupporting
confidence: 88%
“…The average C 2 H 5 I concentration (0.14 pmol l -1 ) was within the range of previously reported values (0.10-0.27 pmol l -1 ) in the Atlantic section of the Southern Ocean (50-60°S) during the austral summer (Abrahamsson et al, 2004). Hughes et al (2008) have reported that biogenic marine aggregates collected in the subarctic Atlantic water, including plankton concentrate, diatom mucilage, and phytodetritus, produce C 2 H 5 I at a high rate (0.31 pmol l -1 h -1 ). The high biological productivity in subpolar water containing high levels of biogenic aggregates would lead to a high rate of C 2 H 5 I production in seawater.…”
Section: Distributions Of C 2 H 5 I Concentration and Sea-to-air Fluxsupporting
confidence: 88%
“…Figure 6 shows halocarbon profiles through the full depth of the water column at the ice station. Profiles of C 2 H 5 I, and C 3 H 7 I show a strong peak at 10 m, just above the mixed layer depth at 12 m. Previous measurements [Hughes et al 2008] have shown these halocarbons can be produced in marine aggregates which are likely to collect here, as they sink from the upper photic zone due to gravity, but are prevented from sinking further due to the pycnocline barrier. CH 2 Br 2 is the only halocarbon which shows a similar profile to Chl a.…”
Section: Halocarbons In Seawatermentioning
confidence: 77%
“…A 9 cm diameter SIPRE corer (Mark II coring system from Kovacs Enterprises 4 nitrogen is difficult to organise (Hughes et al 2008, Hughes et al 2009). Trapping efficiencies were measured and applied to the data.…”
Section: Sample Collection -Sea Ice Brine From Coresmentioning
confidence: 99%
“…These results suggest that halocarbons, such as CH 3 Cl, CH 3 Br, CH 2 ClI, and CH 2 I 2 , were probably not produced by the diatom-dominated bloom at this site and production of these compounds could be affected by species of pico-sized phytoplankton and/or the composition of the assemblage of microorganisms. Hughes et al (2008) reported that volatile iodocarbons were produced from biogenic marine aggregates. Marine aggregates exhibit diversity in organic matter content and microbial composition between different geographic locations and depths in the water column, and this variability could affect the iodocarbon production rate (Hughes et al 2008).…”
Section: (3) Size-fractionated Chlorophyll-a and Methyl Halide Concenmentioning
confidence: 99%
“…Hughes et al (2008) reported that volatile iodocarbons were produced from biogenic marine aggregates. Marine aggregates exhibit diversity in organic matter content and microbial composition between different geographic locations and depths in the water column, and this variability could affect the iodocarbon production rate (Hughes et al 2008). This result also suggests that the composition of microorganisms leads to variations in halocarbon productions.…”
Section: (3) Size-fractionated Chlorophyll-a and Methyl Halide Concenmentioning
confidence: 99%